(untitled) (Desenvolvimento em Questão, 2026)
This article analyzes the actions of different social actors in the territorial articulation of the municipality of Santo Cristo, Rio Grande do Sul, within the framework of the project “Territorial Heritage as a Reference in the Process of Territorial or Regional Development” (ProPAT). The main objective is to understand the perceptions of various social actors regarding institutional representativeness, interinstitutional cooperation, citizen participation, and the effectiveness of public services. A structured questionnaire with a percentage scale (0% to 100%) was used, applied in person to 33 respondents previously selected based on their social engagement and institutional experience in the municipality. During the application, the researchers sought not only to collect objective answers but also to capture spontaneous observations and comments, allowing the integration of interpretative nuances and contextual impressions into the analysis. This methodological approach—combining questionnaire administration and listening to participants’ — made it possible to gather both quantitative information and qualitative perceptions, thereby enriching the interpretive depth of the study. The data were organized using an approach inspired by Discursive Textual Analysis, enabling the systematization of perceptions into thematic nuclei related to representativeness, participation, cooperation, and quality of public services. This is an exploratory analysis whose initial results provide relevant insights for understanding trends, potentialities, and challenges of local territorial articulation, as well as for guiding future stages of the ProPAT and deepening qualitative investigations.